PENGARUH MODEL THINK PAIR SHARE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA IPAS KELAS V SD NEGERI 204 PALEMBANG - Ariyanti, Tika; Diah Budi Setyaningrum, Naomi; Puspita Sari jaya, Melinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking ability is one of the important abilities that students need to have in learning. However, in social studies learning in grade V, students' critical thinking ability is still relatively low because learning is still conventional so that students are less active in discussing and expressing opinions. This study aims to determine the effect of the Think Pair Share model on the critical thinking ability of fifth-grade social studies students at SD Negeri 204 Palembang. This study used an experimental method with a pretest - posttest control group design. The research sample consisted of 52 students consisting of 26 students in the experimental class and 26 students in the control class. The instrument used was a test to measure critical thinking ability. The results showed that the average value of the experimental class was 81.60 while the control class was 65.65. The results of the hypothesis test using the t test obtained a significance value of 0.003 <0.05, so Ho was rejected and Ha was accepted. Based on these results, it can be concluded that there is an effect of the Think Pair Share learning model on the critical thinking ability of fifth-grade students on the material of human growth stages at SD Negeri 204 Palembang.